PERBANDINGAN EFISIENSI BIAYA DAN KINERJA KEUANGAN PERUSAHAAN FARMASI YANG TERLIBAT DALAM PENGADAAN VAKSIN COVID-19 DI INDONESIA PADA SEBELUM DAN SELAMA PANDEMI COVID-19 (Studi Kasus pada PT Bio Farma (Persero), PT Kimia Farma Tbk, dan PT Indofarma Tbk) - Rizki Fadzilatunisa; Endang Kiswara (Diponegoro Journal of Accounting, 2022)
This study aims to compare the cost efficiency and financial performance of pharmaceutical companies involved in procuring the Covid-19 vaccine before and during the Covid-19 pandemic in Indonesia. These companies consist of PT Bio Farma (Persero), PT Kimia Farma Tbk, and PT Indofarma Tbk. This study refers to the research of Isik and Uygur (2021) which uses the Data Envelopment Analysis (DEA) approach to measure cost efficiency which consists of technical efficiency, allocative efficiency, pure technical efficiency, and scale efficiency. Moreover, to measure financial performance, this study refers to the research of Yuniarti, Paryanti, and Tejaningsih (2020) through 3 financial ratios which the authors then expand into 10 financial performance ratios consisting of the current ratio, acid test ratio, inventory turnover ratio, fixed assets turnover ratio, debt to assets ratio, debt to equity ratio, net profit margin, gross profit margin, return on investment and return on equity. This study uses a comparative quantitative descriptive method. This study compares the ratios of cost efficiency and financial performance of companies using cross-sectional methods and time series analysis through descriptive statistical explanations. The results showed that the average company experienced an increase in cost efficiency during the pandemic. The increase in cost efficiency was due to the increase in technical efficiency which was higher than the decrease in allocative efficiency. The technical inefficiency experienced by the average company stems from the scale inefficiency because it is known that pure technical efficiency is constant before and during the pandemic. In contrast to Bio Farma and Kimia Farma which have optimal efficiency values, Indofarma is the only company that experienced inefficiency for two periods. Another finding in this study is that the average company's financial performance decreased during the Covid-19 pandemic. In 2019, Bio Farma had the highest ratio of CR, NPM, GPM, ROI, and ROE, and Indofarma had the highest ratio of ATR, ITR, FATR, DAR, and DER. Moreover, in 2020 Bio Farma has the highest ratio of ATR, NPM, GPM, ROI, and ROE, and Indofarma has the highest ratio of CR, ITR, FATR, DAR, and DER. Based on the overall financial performance ratio, Indofarma was superior both before and during the pandemic and was a company that experienced positive growth during the Covid-19 pandemic.